2009
DOI: 10.1111/j.1468-3148.2008.00468.x
|View full text |Cite
|
Sign up to set email alerts
|

Emergency Psychiatric Services for Individuals with Intellectual Disabilities: Caregivers’ Perspectives

Abstract: Background Strains on the mental health system and inaccessible services for individuals with intellectual disabilities (ID) often force caregivers to bring individuals with ID to the emergency department (ED) when in psychiatric crisis. The purpose of this study was to understand the experience of caregivers and adults with ID and mental health issues, according to caregivers' perspectives. Method Focus groups were conducted with one group of unpaid caregivers (i.e. family members) and two groups of paid care… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
37
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 42 publications
(38 citation statements)
references
References 42 publications
1
37
0
Order By: Relevance
“…They visit hospital EDs frequently, even though the ED is not an ideal environment for them. 7,25,26 As severity of psychiatric comorbidity increases, ED use cannot simply be attributed to poor access to either primary or psychiatric care. Rather, increased ED use among people with DD and concurrent psychiatric illness occurs despite reasonable access to primary care and specialty services, compared with access by people without DD.…”
Section: Discussionmentioning
confidence: 99%
“…They visit hospital EDs frequently, even though the ED is not an ideal environment for them. 7,25,26 As severity of psychiatric comorbidity increases, ED use cannot simply be attributed to poor access to either primary or psychiatric care. Rather, increased ED use among people with DD and concurrent psychiatric illness occurs despite reasonable access to primary care and specialty services, compared with access by people without DD.…”
Section: Discussionmentioning
confidence: 99%
“…56,57 Problems reported by carers of people with learning disabilities in hospital include ill-defined role boundaries, whereby hospital staff and carers (especially paid carers) are uncertain about what carers can and will do; not being supported to take a break from caring; and lack of recognition for carers' expertise and advocacy role. 56,58 Several studies found that the family's expert knowledge was rarely solicited by hospital staff, 59 and that this had led to compromised safety or increased suffering and pain. 60 Other authors reported that carers felt they needed to be constantly present and vigilant, fearing that in their absence the patient's needs, including basic care needs such as eating, drinking and toileting, would not be met and the patient could be harmed; this fear was often based on past experience.…”
Section: The Roles and Experiences Of Carers In Hospitalsmentioning
confidence: 99%
“…It may also be that some parents expect services to assist them in ways that are not within the capacity of the services. Our previous research has shown that caregivers of people with ID often use the emergency department in times of behavioral crisis, with the hope that it will be able to reduce problems behaviors, and report frustration when the emergency department physician recommends medication to treat problem behaviors instead of a more integrative approach (Weiss et al, 2009). At the same time, emergency department physicians note that as a triage service, there is little else that they can provide in terms of actual intervention, and express frustration over caregivers' expectations .…”
Section: Service Receiptmentioning
confidence: 99%